1996
DOI: 10.1073/pnas.93.14.6975
|View full text |Cite
|
Sign up to set email alerts
|

The C-terminal domain of the largest subunit of RNA polymerase II interacts with a novel set of serine/arginine-rich proteins.

Abstract: Although transcription and pre-mRNA processing are colocalized in eukaryotic nuclei, molecules linking these processes have not previously been described. We have identified four novel rat proteins by their ability to interact with the repetitive C-terminal domain (CTD) of RNA polymerase II in a yeast two-hybrid assay. A yeast homolog of one of the rat proteins has also been shown to interact with the CTD. These CTD-binding proteins are all similar to the SR (serine/arginine-rich) family of proteins that have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
276
0
3

Year Published

1998
1998
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 324 publications
(292 citation statements)
references
References 46 publications
13
276
0
3
Order By: Relevance
“…Nrd1 contains a CID (Meinhart and Cramer 2004;Meinhart et al 2005) that interacts with CTD phosphorylated at Ser5 (Conrad et al 2000;Gudipati et al 2008;Vasiljeva et al 2008a). Nrd1 also interacts with another essential RNA-binding protein, Nab3 (Yuryev et al 1996). Nrd1, Nab3, and Sen1 form the Nrd1 complex, which is detected by ChIP at snoRNAs genes (Kim et al 2006) as well as some mRNAs genes, mainly at promoter regions (Nedea et al 2003).…”
Section: The Nrd1 Complexmentioning
confidence: 99%
See 1 more Smart Citation
“…Nrd1 contains a CID (Meinhart and Cramer 2004;Meinhart et al 2005) that interacts with CTD phosphorylated at Ser5 (Conrad et al 2000;Gudipati et al 2008;Vasiljeva et al 2008a). Nrd1 also interacts with another essential RNA-binding protein, Nab3 (Yuryev et al 1996). Nrd1, Nab3, and Sen1 form the Nrd1 complex, which is detected by ChIP at snoRNAs genes (Kim et al 2006) as well as some mRNAs genes, mainly at promoter regions (Nedea et al 2003).…”
Section: The Nrd1 Complexmentioning
confidence: 99%
“…ChIP analysis showed RNAPII read-through at most snoRNAs genes in a SEN1 mutant strain or a strain defective for its helicase activity (Kim et al 2006;Steinmetz et al 2006b). Sen1 associates with the CTD and also coprecipitates with several snoRNAs and some snRNAs (Yuryev et al 1996;Ursic et al 1997Ursic et al , 2004. Nedea et al (2008) showed that Glc7, the yeast PP1 (protein phophatase-1) catalytic subunit, is also a regulator of snoRNA termination, interacting directly with Sen1.…”
Section: The Nrd1 Complexmentioning
confidence: 99%
“…Band`a' represents Hsp73, which may signify an artifact of our system as the ER domain interacts with the very closely related Hsp70 protein (Smith and Toft, 1993). Band`b' includes a clone for an RNA polymerase II-binding protein (Yuryev et al, 1996) and a clone for subunit of RNA polymerase III (Sepehri and Hernandez, 1997), both of which potentially regulate cell proliferation. Another clone isolated from band`b' encodes fau, an arsenateresistance protein which is also a tumor suppressor (Rossman and Wang, 1999).…”
Section: Inhibition Of Cbf Decreases Cdk4 Levelsmentioning
confidence: 99%
“…These early genomic efforts suggested that, similar to DNA binding proteins, functional groupings of genes are being bound by RNA binding proteins perhaps as post-transcriptional operons (Keene and Tenenbaum 2002). However, it is not known at which stage of RNA processing these operons are established.Much of pre-mRNA processing is coupled to transcription both physically and functionally, potentially through interactions with the C-terminal domain (CTD) of RNA polymerase II (RNA Pol II) (Mortillaro et al 1996;Yuryev et al 1996;Kim et al 1997). The CTD is phosphorylated as transcription begins.…”
mentioning
confidence: 99%